Silica-immobilized Aquivion PFSA superacid: application to heterogeneous direct etherification of glycerol with n-butanol1. Issue 8 (21st August 2015) - Fang, Wenhao; Wang, Sheng; Liebens, Armin; De Campo, Floryan; Xu, Hualong; Shen, Wei; Pera-Titus, Marc; Clacens, Jean-Marc
<x xml:space="preserve">Abstract</x> Silica-immobilized Aquivion® resin with high mesoporosity and acid-site accessibility demonstrated good activity, selectivity and reusability for glycerol etherification with n-butanol.